Inefficiencies identified in healthcare professional-to-patient handover practices for atrial fibrillation: a mixed-methods study in Brazil, China and Sri Lanka - Gooden, T.E.; Wang, J.; Goulart, A.C.; Vethanayagam, S.A.; Wang, H.; Varella, A.C.; Paschoal, E.; Powsiga, U.; Shribavan, K.; Shivany, S.; Zhang, H.; Zhong, J.; et al. (BMJ Global Health, 2025)
Introduction Information continuity and self-care are important for optimal management of atrial fibrillation (AF) to reduce complications (eg, stroke) and improve prognosis and patient satisfaction. This can be achieved through handover of information from healthcare professionals (HCPs) to patients. In Brazil, China and Sri Lanka, we conducted a mixed-methods study to identify cross-country differences, similarities, barriers and facilitators regarding HCP-to- patient handover on AF. Adults (≥18 years) with AF who spoke the local languages were included. Anyone with hearing or cognitive impairment was excluded. A questionnaire was administered and focus group discussions (FGDs) conducted. χ2 tests identified differences within and between countries on use of patient-held health records (PHRs); a content analysis identified perspectives and experiences of HCP-to- patient handover. Data were then triangulated using a convergence model to compare and contrast quantitative and qualitative findings to identify barriers and facilitators for improving HCP-to- patient handover. 716 participants completed the questionnaire and 13 FGDs were conducted. People with AF receive a range of information on living with AF and AF management, though information given varies between countries. All three countries had PHRs, and most patients said they were important and were used by doctors; however, PHRs were inconsistently given to patients and updated by doctors. Although patients valued the information provided, PHRs were not often used for their dual purpose (self-care and information continuity), and often, patients used external sources for seeking additional information which was difficult for disadvantaged patients, particularly in China. Conclusion Our findings highlight inefficiencies of HCP-to- patient handover for AF that have implications on healthcare and patient safety in low- and middle-income countries (LMICs). A global standard is needed to describe what information PHRs should include. Additionally, HCPs and patients should be informed on how to optimise PHRs and handover practices to improve self-care, support, prognosis and healthcare resilience of AF care in LMICs.